2001
DOI: 10.1016/s1567-1356(01)00021-6
|View full text |Cite
|
Sign up to set email alerts
|

Zygosaccharomyces kombuchaensis, a new ascosporogenous yeast from 'Kombucha tea'

Abstract: A new ascosporogenous yeast, Zygosaccharomyces kombuchaensis sp. n. (type strain NRRL YB-4811, CBS 8849), is described; it was isolated from Kombucha tea, a popular fermented tea-based beverage. The four known strains of the new species have identical nucleotide sequences in domain D1/D2 of 26S rDNA. Phylogenetic analysis of D1/D2 and 18S rDNA sequences places Z. kombuchaensis near Zygosaccharomyces lentus. The two species are indistinguishable on standard physiological tests used for yeast identification, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…The second group includes other species currently assigned to Zygosaccharomyces that are not part of the Z. rouxii clade, on the basis of rDNA analysis, viz. Z. cidri, Z. fermentati, Z. florentinus, Z. microellipsoides and Z. mrakii (Kurtzman et al, 2001). Based on multi-gene sequence analysis, Kurtzman recently reviewed the genus, splitting the 11 Zygosaccharomyces species into three phylogenetically circumscribed genera, viz.…”
Section: Solieri S Cassanelli and P Giudicimentioning
confidence: 99%
See 1 more Smart Citation
“…The second group includes other species currently assigned to Zygosaccharomyces that are not part of the Z. rouxii clade, on the basis of rDNA analysis, viz. Z. cidri, Z. fermentati, Z. florentinus, Z. microellipsoides and Z. mrakii (Kurtzman et al, 2001). Based on multi-gene sequence analysis, Kurtzman recently reviewed the genus, splitting the 11 Zygosaccharomyces species into three phylogenetically circumscribed genera, viz.…”
Section: Solieri S Cassanelli and P Giudicimentioning
confidence: 99%
“…Nine species are currently accepted in the genus (Kurtzman, 1998) and recently two new species, Z. lentus (Steels et al, 1999) and Z. kombuchaensis, have been proposed (Kurtzman et al, 2001;Steels et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the genus Kodamaea Yamada, Suzuki, Matsuda et Mikata was proposed for that species (Yamada et al 1995b). In this study, Kodamaea ohmeri also found in A. florea, showed a strong (Kurtzman and Robnett 1998;Kurtzman et al 2001;Rosa and Lachance 2005;Steels et al 1999). Bootstrap values were calculated from 1,000 replicates, and values below 50% were omitted.…”
Section: Resultsmentioning
confidence: 67%
“…Identification of yeast other than Candida was performed by ethanol tolerance test (Guimarães et al, 2006). Acetic acid tolerance test was also performed using acidified media (Kurtzman et al, 2001). …”
Section: Biochemical Characterization Of Yeastmentioning
confidence: 99%